Immunogenicity of AS03-adjuvanted and non-adjuvanted trivalent inactivated influenza vaccines in elderly adults: A Phase 3, randomized trial and post-hoc correlate of protection analysis. Issue 12 (1st December 2016) - Ruiz-Palacios, Guillermo M.; Leroux-Roels, Geert; Beran, Jiri; Devaster, Jeanne-Marie; Esen, Meral; Launay, Odile; McElhaney, Janet E.; van Essen, Gerrit A.; Benoit, Anne; Claeys, Carine; Dewé, Walthère; Durand, Christelle; et al.
ABSTRACT: In this study we describe the immunogenicity results from a subset of older people (N = 5187) who participated in a Phase 3 randomized, observer-blinded trial of AS03-TIV versus TIV ( Fluarix ™) (ClinicalTrials.gov, NCT00753272). Participants received one dose of AS03-TIV or TIV in each study year and antibody titers against the vaccine strains were assessed using hemagglutination-inhibition (HI) assay at 21 d and 180 d post-vaccination in each vaccine group in the 2008/09 (Year 1) and 2009/10 (Year 2) influenza seasons. Manufacturing consistency of 3 lots of AS03-TIV for HI antibody responses in Year 1 was a co-primary objective. In a post-hoc analysis, a statistical regression model included 4830 subjects in whom immunogenicity and laboratory-confirmed attack rate data were available; the analysis was performed to assess HI antibody titers against A/H3N2 as a correlate of protection for laboratory-confirmed A/H3N2 influenza. AS03-TIV and TIV elicited strong HI antibody responses against each vaccine strain 21 d post-vaccination in both years. The manufacturing consistency of 3 lots of AS03-TIV was demonstrated. In both years and each vaccine group, HI antibody responses were lower for A/H1N1 than the other vaccine strains. Day 180 seroconversion rates (proportion with ≥4-fold increase in titer compared with pre-vaccination titer) in Year 1 in the AS03-TIV and TIV groups, respectively, were 87.7% and 74.1% for A/H3N2, 69.7% and 59.6% for influenza B, and 58.3% and 47.4% for A/H1N1. The post-hoc statistical model based on A/H3N2 attack rates and HI antibody titers estimated that a 4-fold increase in post-vaccination titers against A/H3N2 was associated with a 2-fold decrease in the odds of A/H3N2 infection.